Предмет: Алгебра,
автор: Называйбелкой
решите (х-2)(х^2+1)=2(х^2+1) пожалуйста
Ответы
Автор ответа:
0
( Х - 2 )( х^2 + 1 ) = 2( х^2 + 1 )
( Х - 2 )( х^2 + 1 ) - 2( х^2 + 1 ) = 0
( х^2 + 1 )( Х - 2 - 2 ) = 0
( х^2 + 1 )( Х - 4 ) = 0
Х^2 + 1 = 0
Нет решений
Х - 4 = 0
Х = 4
Ответ 4
( Х - 2 )( х^2 + 1 ) - 2( х^2 + 1 ) = 0
( х^2 + 1 )( Х - 2 - 2 ) = 0
( х^2 + 1 )( Х - 4 ) = 0
Х^2 + 1 = 0
Нет решений
Х - 4 = 0
Х = 4
Ответ 4
Похожие вопросы
Предмет: Биология,
автор: Аноним
Предмет: История,
автор: Аноним
Предмет: Математика,
автор: denis1600554
Предмет: Геометрия,
автор: sevasvlada
Предмет: Биология,
автор: 7454648